2008
DOI: 10.1080/09638280801906081
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet rich plasma for arthroscopic rotator cuff repair. A pilot study

Abstract: No adverse events related to this application were noted during the procedure. The application of platelet rich plasma during arthroscopic rotator cuff repair is safe and effective, and produces results which seem to be stable with time. A prospective randomized investigation will be necessary to ascertain the efficacy of platelet rich plasma application to improve or expedite the surgical outcome following arthroscopic rotator cuff repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
144
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(159 citation statements)
references
References 22 publications
3
144
0
12
Order By: Relevance
“…The results, although irregular, don't improve the ones obtained when autograft is used [1,15,22]. The clinical experience is even more contradictory.…”
Section: Discussionmentioning
confidence: 90%
“…The results, although irregular, don't improve the ones obtained when autograft is used [1,15,22]. The clinical experience is even more contradictory.…”
Section: Discussionmentioning
confidence: 90%
“…For each growth factor, levels in the subacromial space were markedly higher than levels in the serum. These observations indicate growth factors may be equally important during the beginning of the healing process as toward the end [44].…”
Section: Biology Of Bone-to-tendon Healingmentioning
confidence: 81%
“…A total of 14 patients undergoing arthroscopic repair of a rotator cuff tear received an intraoperative application of autologous PRP in combination with an autologous thrombin component after tear repair. The authors concluded application of PRP during arthroscopic rotator cuff repair is safe and effective, without any adverse events [44]. Further prospective studies are needed to investigate the effect of PRP on rotator cuff healing and ultimate shoulder function.…”
Section: Growth Factor Additionmentioning
confidence: 89%
See 2 more Smart Citations